EDUCATIONAL LACK OF WOMEN IN OKKY MADASARI’S ENTROK - Nurul Rahmawati; Dian Nurrachman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
This research is aims to know how educational lack of women in the novel entitled Entrok by Okky Madasari. Entrok is a novel by Okky Madasari which contains various issues, one of which is the issue of feminism. This novel also shows life in old tradition in a village where everything is far from modern, where women are completely blocked by the tyranny of men and labeled as 'weak'. The theory used in this research is theory feminism by Mary Wollstonecraft. And the result showed that not everyone can get an education, like Sumarni and Simbok in this Entrok novel. And more than that, the position of a woman when she does not have an educational background, she will be increasingly under men and make her have a 'weak character'. This be accordance with Mary Wollstonecraft, she expressed her view that the 'weakness' of women is due to the lack of education that women get and women's pleasure in reading or watching picisan. So that makes women put their feelings first.